Erlotinib-Modified BODIPY Photosensitizers for Targeted Photodynamic Therapy - Gul, Elif Yildiz; Karatas, Elanur Aydin; Dogan, Hatice Aydin; Karatas, Omer Faruk; Cosut, Buenyemin; Ecik, Esra Tanriverdi (Wiley-V C H Verlag Gmbh, 2023)
Photodynamic therapy (PDT) is an innovative, non-invasive and highly selective therapeutic modality for tumours and non-malignant diseases. BODIPY based molecules can function as new generation photosensitizers (PSs) in various PDT applications. Despite numerous conjugated PS systems are available, BODIPYs containing erlotinib lagged behind other photosensitizer units. In this study, smart photosensitizers containing BODIPY, erlotinib and hydrophilic units were prepared for the first time, their physicochemical properties and PDT effects were investigated. Compared with non-halogenated compound, halogenated derivatives possessed much lower fluorescence profile as well as the good ROS generation ability under red light. In vitro PDT studies were performed on both healthy (PNT1a) and prostate cancerous cells (PC3) to determine the selectivity of the compounds on cancerous cells and their effects under light. The halogenated conjugates, exposed to low dose of light illumination exhibited potent activity on cancer cell viability and the calculated IC50 values proved the high phototoxicity of the photosensitizers. It was also determined that the PSs have very low dark toxicity and that the light illumination and ROS formation are required for the initiation of the cell death mechanism. As a result, erlotinib modified BODIPYs could serve as promising agents in anticancer photodynamic therapy.
Keywords: BODIPY; photosensitizers; photodynamic therapy; singlet oxygen